Pengenalan Bahasa Inggris pada Anak Usia Dini di Sekolah Gratis Raudlatul Athfal Ben Pinter Semarang - Sri Wuli Fitriari; Alief Noor Farida; Christianti Tri Hapsari; Woro Apriliana Sari; Yusi Rahmawati; Nadya Zulfa Chairunnisa (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Raudhatul Athfal Ben Pinter was established to provide accessible early childhood education for underprivileged families in Dukuh Jamalsari, Mijen District, Semarang City. Since its establishment, the school has never offered English lessons, although the head of the madrasah and teachers hoped that children in their Golden Age could access free English learning. Limited teacher competence in English became a major obstacle. This community service program was carried out to introduce English to students in a fun and engaging way through modeling, drilling, singing, games, and real-life communication supported by attractive learning media. The basic materials taught included family, colors, greetings, body parts, and simple conversations using technology-assisted communicative language teaching. Teachers were also involved throughout the activities to strengthen their teaching capacity. The implementation of this program generated positive outcomes, increasing students’ familiarity with basic English vocabulary and supporting teachers’ readiness to continue similar activities. Overall, the English introduction initiative provided meaningful benefits for students, teachers, and the school community.